L'arrivée des familles d'anciens supplétifs dans la région Midi-Pyrénées après 1962. État des lieux - Abderahmen Moumen (Les Cahiers de Framespa)
This paper proposes to review the current state of the settlement of Harkis in Midi-Pyrénées. It examines the context of therepatriation of the French from Algeria and Harkis at a national and regional level, and then presents the spaces of settlement of the families of former auxiliaries in Midi-Pyrénées : the camp of Larzac and the forestry hamlets.